Strategic Approach of Managing Violence During Recreational Sports Events in Ado-Odo/Ota Local Government Area, Ogun State, Nigeria - Ibraheem Tajudeen Olanrewaju; Abdurahman Owoade (Indonesian Journal of Sport Management, 2022)
This study examined strategic approach of managing violence during recreational sport events in Ado-Odo/Ota Local Government area, Ogun state, Nigeria. descriptive design of survey type was employed with a population of 144 respondents sampled purposively for the research. A researcher structured questionnaire of strategic management of violence during recreational sports (qsmvdrse) of 4 Likert scale, validated by three experts in Human Kinetics and tested for reliability was used to collect data from respondents. The postulated hypotheses were tested at 0.05 alpha level using Pearson’s Product Moment Correlation Co-efficient. The results (0.320 > 0.147 at df = 142), (0.240> 0.147 at df = 142) and (0.310> 0.147 at df = 142) respectively revealed that Facilities, Organizational Pattern and community involvement are correlates of management of recreational sport violence. I was concluded that availability of Facilities, good organizational pattern and community involvement leads to reduction or eradication of violence during recreational sports events. By this, it was recommended that new facilities should be built while old ones are upgraded to standard, previous events should be properly evaluated, community heads, parents, community security outlets and other stakeholders should be included in the organization and planning of sports event.